Impact of Sex-Related Differences in Infrarenal Aortic Neck Morphology on Outcomes of Endovascular Aneurysm Repair for Similar-Sized Aortic Aneurysm - Ombretta Martinelli; Antonio Marzano; Maria Irene Bellini; Roberto Gattuso; Luca Di Marzo; Valeria Gonta; Jihad Jabbour; Wassim Mansour; Simone Cuozzo (Diagnostics)
Objectives: This study aimed to evaluate whether gender-related anatomical differences in proximal aortic neck morphology affect the feasibility and outcomes of endovascular aortic aneurysm repair (EVAR) in women with abdominal aortic aneurysms (AAA). Methods: This study performed a retrospective analysis of patients electively treated by EVAR for infrarenal AAA between January 2019 and December 2023. Demographics, anatomical characteristics, and stent graft details were analyzed. The primary endpoint was technical success. Secondary endpoints included freedom from aortic and neck-related reinterventions, endoleak rate, and freedom from aneurysm-related mortality during follow-up. Technical aspects, including adherence to the instructions for use (IFUs), were retrospectively analyzed. Results: One-hundred-seventeen patients (fifty-six females; mean age 76.2 ± 5.3 years) underwent elective EVAR for AAA. Demographics and comorbidities were homogeneous across genders. Female patients (Group A) demonstrated a higher prevalence of hostile proximal aortic neck features, including neck length < 10 mm and angulation > 60° (p = 0.009, p = 0.029, respectively) and a higher frequency of off-label EVAR procedures (28.6% vs. 11.5%; p = 0.034). The overall technical success rate was 98.3%, with no significant differences between genders in terms of stent graft selection, use of suprarenal fixation, or incidence of type 1–3 endoleaks. The median follow-up period was 35.2 ± 12.7 months, showing comparable rates of neck-related reinterventions, open conversions, and aneurysm-related mortality between genders. Notably, off-label EVAR was identified as an independent risk factor for type 1A endoleaks, reinterventions, and aneurysm-related mortality (p < 0.00001, p < 0.0001, and p = 0.001, respectively). Conclusions: Female patients undergoing EVAR often present with hostile proximal aortic neck features and are treated at an older age than males. Despite these differences, technical success rates and mid- to long-term outcomes were comparable between genders, with no variation in stent graft selection or suprarenal fixation use. Effective procedural planning, device selection, and surgical expertise appear to mitigate historical gender-related anatomical challenges. Further large-scale studies are needed to confirm whether anatomical factors alone drive outcomes, irrespective of gender.